ANTHROPOLOGICAL-MANAGERIAL INTEGRATION: EXPLORING COLLECTIVE ORGANIZATIONAL VALUES WITHIN THE FRAMEWORK OF STRATEGIC ADAPTATION - Achmad Luthfi Chamidi; Ashlihah Ashlihah; Ahmad Hanif Fajrin; Dede Nurohman; Prim Masrokan Mutohar (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study aims to explore the synergistic relationship between the anthropological and managerial dimensions of organizational culture as an instrument of strategic adaptation. Amid global disruption, organizations often fail to transform not because of poor strategic planning, but because of neglecting their anthropological